2012
DOI: 10.1002/jmri.23703
|View full text |Cite
|
Sign up to set email alerts
|

Negative predictive value for cancer in patients with “Gray‐Zone” PSA level and prior negative biopsy: Preliminary results with multiparametric 3.0 tesla MR

Abstract: Because of the high NPV, MRI had the potential to avoid unnecessary biopsy in approximately one-third of "gray-zone" patients with a negative examination. Additionally, MRI was useful to address to biopsy more than one-third of patients with cancer or high-risk lesions as HGPIN and ASAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…In the study of Girometti et al , which presented a similar study design and the same patients' ethnicity of our study, a comparable cancer incidence was reported (18% versus 19%). However, comparison of results is not reliable, because they reported data from every performed technique only on a per‐region analysis, while a per‐patient analysis was performed only on the overall MRI exam, including dynamic technique.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the study of Girometti et al , which presented a similar study design and the same patients' ethnicity of our study, a comparable cancer incidence was reported (18% versus 19%). However, comparison of results is not reliable, because they reported data from every performed technique only on a per‐region analysis, while a per‐patient analysis was performed only on the overall MRI exam, including dynamic technique.…”
Section: Discussionsupporting
confidence: 85%
“…Correlating our results with those reported by similar studies performed in a population with PSA between 4 and 10 ng/mL is not reliable, because to our knowledge there are few reports on this topic presenting different inclusion criteria and study design (prospective/retrospective), different demographic characteristics (particularly on cancer incidence), different MRI multiparametric techniques (including or not DWI, MRS, dynamic MRI), and different analysis of data (per region‐basis, per half‐gland basis, per patient basis). Moreover, many of these studies do not report Gleason scores derived from biopsy.…”
Section: Discussioncontrasting
confidence: 45%
“…More recently, Girometti et al reported an NPV of 100% for a series of eight men with previous negative biopsy using DWI in addition to T2‐weighted imaging and MRSI before biopsy. When analysed on a per‐region (rather than per‐patient) basis, with each prostate divided into eight standardized regions, T2‐weighted imaging, DWI and MRSI had NPVs of 97, 96 and 94%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…14 MP-MRI has a high negative predictive value for cancer at PSA 2.5 to 10 ng/ml but the performance of MRI/US fusion guided biopsy to discriminate clinically indolent from aggressive disease across a PSA range is unknown. 21 Identifying values above which the detection of clinically significant disease is maximal may be useful to avoid potentially unnecessary and costly MP-MRI and targeted biopsy. In this study patients who underwent targeted plus 12-core TRUS biopsies were stratified by PSA to determine a threshold for performing MP-MRI and fusion biopsy.…”
Section: Discussionmentioning
confidence: 99%